2022
DOI: 10.3390/risks10050094
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Crisis among Inflation Targeting Countries in Sub-Saharan Africa

Abstract: The exchange market pressure index has proven to be a major indicator in identifying exchange rate crises in economies; however, due to the complexities surrounding developing economies, the efficacy of the index has been called to question. Specifically, the selection of an appropriate index and the problem of selecting the appropriate threshold for identifying exchange market pressure. To investigate this issue, this study identifies exchange rate crisis episodes in South Africa and Ghana using ridge regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Aizenman and Binci [26], find that differences in EMPs (Exchange Market Pressure) faced among nations during the financial crisis can be fairly attributed to the differences in per capita income, inflation, and trade balance before it. Klutse, et al [27] adopt Dynamic Ordinary Least Squares, District threshold and ridge regression and the study found that the variables representing the maximum threshold were significantly divergent; thus, affirming the difference between both indexes. Similarly, it was revealed that South Africa had 31 and 27 crises episodes when the first and second lags of EMP were used as dependent variables, with the greatest responses occurring in 2008, the latter period of 2011 to the first quarter of 2012, 2013 and 2015.…”
Section: Empirical Literaturementioning
confidence: 95%
“…Aizenman and Binci [26], find that differences in EMPs (Exchange Market Pressure) faced among nations during the financial crisis can be fairly attributed to the differences in per capita income, inflation, and trade balance before it. Klutse, et al [27] adopt Dynamic Ordinary Least Squares, District threshold and ridge regression and the study found that the variables representing the maximum threshold were significantly divergent; thus, affirming the difference between both indexes. Similarly, it was revealed that South Africa had 31 and 27 crises episodes when the first and second lags of EMP were used as dependent variables, with the greatest responses occurring in 2008, the latter period of 2011 to the first quarter of 2012, 2013 and 2015.…”
Section: Empirical Literaturementioning
confidence: 95%